Blue Laser Optical NOMA Communication Applied on Control Drone-to-Underwater Vehicle - Sameer Sami Hassan Al-Obaidi (Al-Iraqia Journal for Scientific Engineering Research)
Today deep ocean life has not been discovered by humans including many secret world things to be explored. The researcher has focused on underwater optical wireless communications using various kinds of complex digital Signal processing most of them used in air and starting applied in underwater communication. The Internet of Things (IoT) uses underwater called Internet of Underwater Things (IoUT) applications to explore the underwater world with other devices. However, the difference in concentration between air and water surfaces is not easy making wireless communication more complicated. Visible light passes the water's surface with scattering and distortion inside the water and each color of light has different attenuation the blue laser light has low distortions and scattering which means lower attenuation in water. The Non-Orthogonal Multiple Access (NOMA) is a promising next-generation underwater wireless optical communications technology. Moreover; this technology has many features such as low (power consumption, attenuation, noise, and BER (Bit Error Rate)) with a high bit rate. Therefore;  our research proposes a blue laser optical communication system for drone-to-underwater vehicles by optical NOMA techniques that can support various important applications for marine exploration or inspection, This technology uses an underwater Remote Operating Vehicle (ROV) combined with a Drone to collect data information from deep oceans to study and discover the secret deep ocean underwater world with high-quality video and picture. In addition, studying the effect of different weather and water types on the proposed model.